USING EMPLOYEE PERCEPTIONS FOR ORGANIZATIONAL PERFORMANCE ASSESSMENT - (:unkn) unknown (FUTURE ACAD, 2019)
The aim of this paper is to compare perceptual, objective and joint organizational performance measurement outcomes of nine Turkish public hospitals and provide empirical support for using perceptions of employees other than top-level managers on organizational performance. The data consisting of perceptual measures of hospital performance was collected by a survey instrument which was developed based on the dimensions of the performance assessment tool used in Turkish public hospitals. Objective performance scores were obtained from the hospitals' annual performance assessment reports. A joint metric was then obtained by combining the perceptual measures and the objective measures of the hospital performance and comparisons were made using One-Way ANOVA. The results indicated that perceptual performance did not statistically differ between pairs of physicians, nurses and midwives, clinical support staff and administrative support staff. However, all of the four professional groups had a significantly different perception of performance compared to managers. Moreover, when the hospital groups were ranked based on their mean scores of perceptual performance, joint performance and objective performance the ranking did not change. Having similar results for different groups of hospitals in perceptual, objective and joint performance measures imply that using perceptions of employees from different departments of the hospital on organizational performance could indeed be a close proxy for objective measures. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Employee perceptions; organizational performance; hospitals; health care; FIRM